Biologics in Dermatology - David Chandler; Anthony Bewley (MDPI AG, 2013)
Skin and subcutaneous diseases affect millions of people worldwide, causing significant morbidity. Biologics are becoming increasingly useful for the treatment of many skin diseases, particularly as alternatives for patients who have failed to tolerate or respond to conventional systemic therapies. Biological therapies provide a targeted approach to treatment through interaction with specific components of the underlying immune and inflammatory disease processes. This review article examines the increasing evidence base for biologics in dermatology, including well-established treatments and novel agents.